Percepção de discentes de psicopedagogia sobre a práxis psicopedagógica na educação inclusiva - Lima, Maria Zuleide Medeiros (2017)
Inclusive Education is the theme of this research, which is entitled Perception of psychopedagogy discourses on inclusive education in psychopedagogical praxis. This study aims to analyze the perception of the psychopedagogy discourses of the UFPB, about an inclusive education in the light of psychopedagogical praxis. And as specific objectives, identify as learning difficulties inherent to disabilities, know the strategies used to work as learning disabilities and check the training of human resources in inclusive schools. The research was carried out with 22 students from the psychopedagogy course of the UFPB, who respond to a questionnaire about the content regarding inclusive education, in its psychopedagogical doing. The results indicate that Psicopedagogy students perceive that there are many gaps and working conditions in inclusive schools, there is a lack of investments in material and human contexts, especially a professional qualification for a work of heterogeneity.